Meningkatkan Efisiensi AC Split Wall Melalui Preventive Maintenance pada Metode COP dan EER di PT. Hanjaya Mandala Sampoerna Tbk - Maulana Nugraha Mustika; Yulizan Rizki (Jurnal Teknik Industri dan Elektro, 2026)
Indonesia has a tropical climate, resulting in hot and humid weather throughout the year. This increases the need for air conditioning (AC), especially in various buildings such as offices and production sites. AC plays a crucial role in maintaining user comfort, safety, and health. However, AC components are often not regularly maintained. This study explores the impACt of preventive maintenance on the performance and efficiency of electricity use in a split wall AC cooling system at PT. Hanjaya Mandala Sampoerna Tbk, using the coefficient of performance (COP) and energy efficiency ratio (EER) methods. The results show that COP efficiency increased by 1.44 after maintenance compared to before. EER efficiency increased by 2.83 after maintenance compared to before. Electricity cost efficiency increased by Rp 5,809.25,-.